Testing the relationship between Saturn's ENA and narrowband radio emissions - Kinrade, J.; Badman, S. V.; Paranicas, C.; Jackman, C. M.; Louis, C. K.; O'Dwyer, E. P. (My University, 2023)
Saturn's kilometric radiation (SKR) and Energetic Neutral Atom (ENA) emissions are important remote diagnostics of the planet's magnetospheric dynamics, intensifying during periods of global-scale plasma injection, and displaying charcteristic planetary periodicity. Global-scale ENA signatures have been associated with narrowband radio emissions around 5 and 20 kHz, particularly at evening local times where plasma injections are expected to have moved inwards through the magnetosphere, triggering interchange instabilities. Narrowband radio emission sources are associated with density gradients at the inner edges of the Enceladus plasma torus that promote wave mode conversion, but any radial distance dependence with the ENA emission is untested. We constrain ENA keograms to distances covering the `inner' and `outer' magnetosphere separately, and quantify the correlation between the ENA intensity with narrowband density in the 5 and 20 kHz emission bands. One case study shows a spiral ENA morphology that indicates global-scale plasma injection activity. `Bursts' of narrowband emission coincide with the rotation of ENA enhancements through the dusk-midnight local time sector in the inner magnetosphere, but at earlier times in the outer magnetosphere, consistent with inward of the injected plasma as it drifts around the planet. A second case study with similar observing conditions shows clear 5 kHz radio bursts, but very low levels of ENA detections, indicating that the relationship is not always so general in these data. These results contribute towards our developing picture of how global plasma injection events can innce Saturn's inner magnetosphere, linking together two valuable sources of remotely sensed global emissions, the ENAs and narrowband radio emissions.
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED